Political religion, everyday religion : sociological trends - Repstad, Pål (International Studies in Religion and Society, 2019)
As the title suggests, Political Religion, Everyday Religion: Sociological Trends reflects upon two important trends that have recently emerged in the sociology of religion. Firstly, there is an increasing interest in the interplay between religion and politics. Religion has moved from being almost ignored by sociologists to being acknowledged - some would even say overrated - as an important political factor. Secondly, ordinary people's everyday religion has likewise become an important topic for many researchers. In this book, James Beckford, Inger Furseth and other prominent scholars present critical discussions and empirical studies of both political and everyday religion, and the editor, Pål Repstad, shows how these two trends should enter into a closer dialogue. The book is essential for both students and experienced researchers in the sociology of religion.